PENGARUH SHARIA COMPLIANCE TERHADAP PERKEMBANGAN UMKM DIBANGKALAN - Naila Atiatul Ulya; Ahmad Musadad (PROCEEDING UMSURABAYA, 2022)
The majority of the population in Indonesia conducts trading businesses, one of which is in the culinary field. Not a few of the business actors who do not maintain the cleanliness of their food or place, even though Muslims are encouraged to carry out compliance where activities operate in accordance with Islamic Sharia provisions, both in terms of the process of making food and muamalat. The focus described in this discussion is (1) to find out the implementation of Sharia Compliance on MSMEs in Bangkalan; and (2) to find out the analysis of Sharia Compliance effect on the development of MSMEs in Bangkalan. This research used qualitative research with sociological normative research Islamic law literature and connecting it to the fact in the field. Data was collected through direct observation, interview, and documentation. Data was analyzed in descriptive analytical which provided detail description. Hence, the conclusion is obtained from the analysis of the problems which studied inductively based on a number of empirical data to compile a general explanation and conclude on the phenomenon being studied. The result of this research indicated that several MSMEs in Bangkalan have implemented Sharia principles. The effect of Sharia Compliance is very significant for the development of MSMEs in Bangkalan which can be seen from the opening of branches and the increase in business assets, and because most Madurese people are Muslims and a Muslim is obliged to choose halal and toyyib food.Keywords: Sharia Compliance; Development; MSME